Surgical management of Carcinoma Gall bladder - Ullah, Asad; Khan, Omer Ali; Ullah, Atta (Journal of Postgraduate Medical Institute, 2011)
To evaluate surgical management of Ca gall bladder in patients with gall stones. This prospective study of surgical management of Ca Gall Bladder was conducted in surgical A unit of KTH, peshawar from January 2001 to May 2002. A total number of 24 patients with male to female ratio of 1:2 were treated during this period. Main presentation on admission was jaundice, mass right hypochondrium, in a patient out of 24. The diangosis of Ca Gall bladder was made pre-operatively. In all patient gallstones were present. Four patients underwient cholocystectomy. In these patients gall bladder was opened and a suspicious nodule was found, and the diagnosis was confirmed on histopathology. In twenty patients, there was advanced Ca Gall bladder and only biopsy was taken and histopathology confirmed the diagnosis of adenocarcinoma bladder. one patient died on the 3rd postoperative day. A high incidence of Ca gall bladder (13.7%) in cholcystectomies was found with 100% cholelithiasis. majority of the patients had advanced Ca with metastasis.